2018
DOI: 10.4317/medoral.22310
|View full text |Cite
|
Sign up to set email alerts
|

Osteoradionecrosis prevalence and associated factors: A ten years retrospective study

Abstract: BackgroundOsteoradionecrosis (ORN) is one of the most serious complications of head and neck radiotherapy and is considered a public health problem worldwide. This study aims to determine the prevalence and associated factors of ORN in patients undergoing radiotherapy for head and neck malignancy.Material and MethodsA cross-sectional retrospective study was conducted, in which all medical records of patients undergoing head and neck radiation in the period between 2006 to 2015 (10 years) were examined. Clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0
10

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 19 publications
0
27
0
10
Order By: Relevance
“…The ultimate goal would be to optimize radiation treatment plans and offer patients appropriate counseling for dental management to decrease the risk of ORN. Despite the variability in the nature of published ORN studies, preradiation dental procedures (surgery or tooth extraction) are constantly reported as explainable factors for the development of ORN [6,7,10,11]. In this study, and the large SEER study [13], as significantly higher rate of ORN was observed after postoperative/adjuvant radiotherapy.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…The ultimate goal would be to optimize radiation treatment plans and offer patients appropriate counseling for dental management to decrease the risk of ORN. Despite the variability in the nature of published ORN studies, preradiation dental procedures (surgery or tooth extraction) are constantly reported as explainable factors for the development of ORN [6,7,10,11]. In this study, and the large SEER study [13], as significantly higher rate of ORN was observed after postoperative/adjuvant radiotherapy.…”
Section: Discussionmentioning
confidence: 56%
“…Tobacco exposure increases surgical complications after head and neck surgery resulting in impaired local wound healing [21] adding to the risk of necrosis after surgery and RT. Active smoking and poor dental hygiene have been associated with ORN in previous publications [7,8,10], the two factors being mutually related. In this study, both smoking and pre-RT dental procedures were significantly correlated with the risk of ORN, smoking only borderline in the multivariable analysis, and it could be inferred that one or the other factor would be a pseudo-covariate for the other.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Historical incidence of ORN was high, with older studies showing rates approaching 40%. More recent data suggest rates of 4%–8%, likely due to improved RT techniques, dental care, and recognition of risk factors (Table 1) 2,8‐15,21,23,25,28‐34 such as age, sex, BMI, comorbidities such as diabetes, current use of tobacco and alcohol, primary tumor site, size and stage, quality of dentition, dental extractions, radiation dose and technique, and concurrent chemotherapy 8,11‐13,15‐17,19,20,35,36 …”
Section: Introductionmentioning
confidence: 99%
“…Ostéoradionécrose (ORN) : l'ORN peut être définit comme l'exposition de l'os irradié ne guérissant pas sur une période s'étalant à 3 mois et en absence de persistance ou récidive tumorale [31].La physiopathologie de l'ostéoradionécrose reste non élucidée , la théorie de l'insuffisance vasculaire de Marxs et celle de Delanian concernant le processus fibroatrophique prédominant constituent les plus plausibles [32].Son incidence au niveau mandibulaire varie de 2.6% à 15% [33]. Elle peut survenir suite à l'extraction dentaire, une pathologie parodontale et/ou péri apicale , une prothèse mal adaptée traumatique ou après une intervention chirurgicale [34] et peut se manifester par un changement de la densité osseuse , une destruction et/ou exposition osseuse ,un épaississement anormal des tissus mous ,des ulcères buccaux et drainage de sécrétions purulentes [35]. la modification osseuse asymptomatique et la diminution de la densité osseuse représentent les manifestations de départ sur le plan radiologique et évoluent vers les symptômes pré décrits [35].…”
Section: Introductionunclassified